FORMULASI DAN UJI STABILITAS FISIK FACIAL WASH EKSTRAK ETANOL DAUN MELINJO (Gnetum gnemon L.) DENGAN VARIASI PERBANDINGAN EMULGATOR - Sekti, Beta Herilla; Gadis Aprilianti, Rakhmadani (Institut Teknologi, Sains, dan Kesehatan RS.DR. Soepraoen Kesdam V/BRW, 2024)
Soap is a mixture of sodium compounds with fatty acids used as a body cleansing agent, solid, foam, with or without other additives and does not cause irritation to the skin. One of the soaps often used by the community is facial wash to get rid of acne. One plant that is often used is melinjo leaf (Gnetum gnemon L.). Melinjo leaves contain flavonoid compounds that function as antioxidants that will interfere with the metabolic functions of microorganisms such as bacteria. This study was conducted to determine the physical stability test of melinjo leaf ethanol extract facial wash with variations in emulgator ratio. The emulgators used were Stearate Acid, Na CMC, and Trietylamine. The test results show that the comparison of emulgator variations can affect the stability of the preparation. The physical stability tests carried out include organoleptic test, viscosity test, specific gravity test, pH test, foam height test, and homogeneity test. The test results of Formulation I have met all these requirements, in Formulation II and Formulation III the preparation has not met the requirements of the specific gravity test and viscosity test.